Erasmus+ mobility - Lesjak, Miha (Academica turistica, 2020)
Erasmus+ students represent a large sub-segment of educational tourists, making this segment an attractive market for universities as well as destination marketing organisations. Unfortunately, very little is known about Erasmus+ students' travel behaviour; hence the present study aims at extending empirically supported knowledge about travel behaviour of students during their Erasmus+ mobility. Data was collected via an online survey among all Erasmus+ enrolling students in the academic year 2016/17 in Slovenia. The results show that 93% of the participants travelled during theirmobility. The level of studies aswell as gender affect students' travel behaviour, making the two characteristics immediately useful attributes when targeting Erasmus+ travellers. Based on perceived destination attributes, male students predominantly seek cities with attractive nightlife but female students look for easily accessible cities, which are safe and offer attractive cultural sites. These findings suggest that tourism providers, destination tourism organisations and universities should work hand in hand when designing personalised tourism experiences and their promotion among Erasmus+ students. This is crucial during the phase of planning Erasmus+ mobility, when students choose their destination and host university, as well as during students' Erasmus+ mobility, because Erasmus + students travel during their student mobility.
Keywords: destination attributes; education; Erasmus+ mobility; international students; mednarodne izmenjave; mednarodno sodelovanje; Slovenija; študenti; tourist behaviour; turizem; visoke šole